Health care Expert’s readiness to implement National Unified Medical Records (NUMR) system in the United Arab Emirates; A Qualitative study (Informatica, 2021)
Electronic health records provide a valuable resource to improve health evaluation, surveillance and informs effective clinical decision making. Although electronic medical records (EMR) are introduced in many different settings, yet little is known about the readiness, effectiveness and progress of a centralized information system like NUMR across United Arab Emirates. This study aims to determine the readiness for national unified medical record (NUMR), barriers and challenges from the point of views of experts working in the field of health informatics on daily basis. Semi-structured interviews were conducted with 10 experts using purposive sampling method from different healthcare organizations in the United Arab Emirates. Perceptions of interviewees regarding the readiness for national unified medical record were elicited. Thematic analysis was used to identify the different themes extracted from the interview transcripts. Overall, seven themes emerged after analyzing the transcripts obtained from the respondents. This study is expected to bring countless benefits for all countries that are moving forward toward nationwide and interoperable healthcare platforms. The support for NUMR will make a significant contribution to the health systems across UAE that will ultimately lead to safety, access to single shared records, improved care and coordination, better clinical and decision making, faster engagement, easy and secure access, safety and will save time for other tasks. The future of implementation of NUMR in UAE is promising. Our findings offer beneficial guidelines for consideration in implementing NUMR system across UAE and also helps in the drive to improve healthcare systems nationally.